Aryl hydrocarbon receptor (AHR): "pioneer member" of the basic-helix/loop/helix per-Arnt-sim (bHLH/PAS) family of "sensors" of foreign and endogenous signals. (July 2017) - Nebert, Daniel W.
Abstract: The basic-helix/loop/helix per-Arnt-sim (bHLH/PAS) family comprises many transcription factors, found throughout all three kingdoms of life; bHLH/PAS members "sense" innumerable intracellular and extracellular "signals" — including endogenous compounds, foreign chemicals, gas molecules, redox potential, photons (light), gravity, heat, and osmotic pressure. These signals then initiate downstream signaling pathways involved in responding to that signal. The term "PAS", abbreviation for " per-Arnt-sim " was first coined in 1991. Although the mouse Arnt gene was not identified until 1991, evidence of its co-transcriptional binding partner, aryl hydrocarbon receptor (AHR), was first reported in 1974 as a "sensor" of foreign chemicals, up-regulating cytochrome P450 family 1 (CYP1) and other enzyme activities that usually metabolize the signaling chemical. Within a few years, AHR was proposed also to participate in inflammation. The mouse [ Ah ] locus was shown (1973–1989) to be relevant to chemical carcinogenesis, mutagenesis, toxicity and teratogenesis, the mouse Ahr gene was cloned in 1992, and the first Ahr (−/−) knockout mouse line was reported in 1995. After thousands of studies from the early 1970s to present day, we now realize that AHR participates in dozens of signaling pathways involved in critical-life processes, affecting virtually every organ and cell-type in the animal, including many invertebrates.